(untitled) (International Journal of Innovative Technologies in Economy, 2018)
Animation industry is constantly presented in each tourism activity. It has the purpose to positively affect the tourists and leave the feeling of exclusiveness, uniqueness and unforgettable memories of the trip. Tourism animation has complex nature – it should affect the tourists to take part in animation events without using any compulsion, bring people together through communication, find, direct and develop various types of talents and abilities among the tourists, and etc. Therefore the problems animator is facing require him/her to have different knowledge and skills which should be successfully applied in a particular case. In a way animator’s occupation represents a mixture of the jobs of the teacher, social worker, colleague, friend and all of this should be skilfully combined in one person. Animator should predispose all the tourists, affect them positively, make lots of contacts without neglecting or protecting individuals, be able to entertain and amuse all the tourists in interesting and attractive way. Animator should be able to work in perfect harmony not only with tourists and fellow animators but also with his/her colleagues performing other types of tourism services / accommodation and food / because otherwise a separate animation program could hardly be achieved. The purpose of this article is to demonstrate that animation is no longer an additional service in tourism, but a vital necessity for any tourist complex, providing it with an unique competitive advantage.